2018 Physics Education Research Conference Proceedings 2019
DOI: 10.1119/perc.2018.pr.dounas-frazer
|View full text |Cite
|
Sign up to set email alerts
|

Correlating students' views about experimental physics with their sense of project ownership

Abstract: Multiweek projects in physics labs can engage students in authentic experimentation practices, and it is important to understand student experiences during projects along multiple dimensions. To this end, we conducted an exploratory quantitative investigation to look for connections between students' pre-project views about experimental physics and their post-project sense of project ownership. We administered the Colorado Learning Attitudes About Science Survey for Experimental Physics (E-CLASS) and the Proje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Building on these studies, Enghag found that physics student's motivation to work on miniprojects was positively impacted by their sense of ownership, which in turn had a positive impact on their holistic understanding of physics [6]. More recently, Dounas-Frazer and Lewandowski (2019) used student responses to the Project Ownership Survey (POS) [9] and the Colorado Learning Attitudes about Science Survey for Experimental Physics (E-CLASS) [14,15] to show a positive correlation between students' sense of project ownership and their attitudes about experimental physics [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on these studies, Enghag found that physics student's motivation to work on miniprojects was positively impacted by their sense of ownership, which in turn had a positive impact on their holistic understanding of physics [6]. More recently, Dounas-Frazer and Lewandowski (2019) used student responses to the Project Ownership Survey (POS) [9] and the Colorado Learning Attitudes about Science Survey for Experimental Physics (E-CLASS) [14,15] to show a positive correlation between students' sense of project ownership and their attitudes about experimental physics [16].…”
Section: Introductionmentioning
confidence: 99%
“…In total, 87 students and 4 instructors agreed to participate in one or more aspect of the study. Analyses of subsets of these data have been reported elsewhere [13,16]. Of the 87 student participants, only 15 agreed to participate in post-project interviews.…”
Section: Introductionmentioning
confidence: 99%
“…Our team is particularly interested in studying and supporting lab courses in which students have the opportunity to carry out their own experimental physics projects over multiple weeks. To this end, we have been exploring the construct of student ownership of projects [3][4][5]. Here, we present work in progress toward developing a model for student ownership of projects.…”
Section: Introductionmentioning
confidence: 99%
“…Last, Savery (1996) depicted ownership as consisting of four psychological quadrants: metacognitive and cognitive factors (e.g., constructing knowledge), affective factors (e.g., motivation), personal and social factors (e.g., teamwork skills), and individual factors (e.g., attitude toward learning) [14]. In our model development efforts, we build from these and other prior models for ownership, and we take into account results from recent and ongoing research on student ownership in physics [3][4][5] and other contexts (e.g., Refs. [6,8,13]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation